Learning Management for Productive Technical and Motorcycle Business Subjects at Public Vocational High School 1 Warungasem - Syamsu Haryadi; Ngurah Ayu Nyoman Murniati; Soedjono Soedjono (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2022)
This research was motivated in the midst of limited face-to-face learning restrictions that took place during the covid 19 pandemic, but the Warungasem State Vocational High School 1 was still able to excel in the Student Skills Competition at the Central Java Province, by winning 2nd place for the bicycle engineering and business competition. Motorcycle. This study aims to determine the Learning Management of Productive Subjects of Motorcycle Engineering and Business at Public Vocational High School 1 Warungasem. This study uses qualitative research methods, located at the Public Vocational High School 1 Warungasem. Research time in July 2022. Data collection techniques with the method of observation, interviews, and documentation. Test the validity of the data using triangulation. Data analysis includes: data collection, data condensation, data presentation and drawing conclusions. Research results 1) Planning includes (a) preparing the vision, mission and objectives of skill competence (b) preparing work programs (c) preparing planning for productive practice tools and budgets (d) planning for industrial work practices (e) preparing plans for skill competency tests. 2) Organizing includes: (a) formation of management, (b) division of work tasks according to their respective potentials, (c) standard SOPs for implementing tasks (d) coordination and communication in all fields. 3) Implementation includes: (a) theoretical learning in the classroom and (b) practical learning in practice rooms and industrial internships. 4) Supervision includes: (a) internal supervision is carried out by the Principal, and the Deputy Head of Curriculum. (b) external supervision is carried out by Supervisors from the Branch Office of Education Region XIII. Keywords: management, productive learning, motorcycle business engineering